Village's Direct Cash Assistance Actualization - Gestianan, Putri Stevia (Universitas Sebelas Maret (UNS), 2022)
Covid-19 Pandemic affects significantly not only in global health but also a massive efcect in economy. Therefore, to minimize a larger effect, Indonesian government imement few policies that orients on national economy stabilization. One of the policies mentioned is Village Ministry Rule PDTT No. 13 Year 2020, which dictates a village direct cash Assistance. The program acts as a social safety net which draws from each village funds. The purpose is to maintain the public buying power amidst the Pandemic. To study the implementation and factors, the researcher conducts their research on Bumiharjo village. This research uses qualitative methods in Bumiharjo village, Glenmore residence, Banyuwangi, with a focus on implementation of direct cash Assistance program in 2021 and ITS affecting factors. The purpose of this research is to describe and analyze the implementation of direct cash Assistance program in Bumiharjo village in 2021.